고무 인상채득시 지대치재료와 표면처리법의 영향 - 정도진; 양홍서; Jeong Do-Jin; Yang Hong-So (Taehan Chikwa Poch'ol Hakhoe chi, 2001)
The purpose of this study was twofold. One was to evaluate the wettability of 4 elastomeric impression materials on tooth and different kinds of filling materials. The other was to identify the effect of topical surfactants sprayed on the surface of each impression. The elastomeric impression mate rials used in this experimental study were one polyether(Impregum F) and three polyvinyl siloxanes(Provil novo, Zerosil, Imprint). The abutments were prepared for 3/4 crown or onlay on the extracted human first molar. The filling materials used in this study for the duplication of prepared abutment were composite resin, amalgam, and casting metal. Impression was taken by manufacturer's recommendations and the number of voids on the impression surface was counted. The topical surfactants were Spannex $II^{(R)}$ and $Cohere^{(R)}$. The wettability was evaluated by comparing the number of voids between non-treated group and treated groups. The results were as follows : 1. $Zerosil^{(R)}$ showed the least number of voids on the impression surface. The number of voids increased in order of Provil $novo^{(R)}$, Impregum $F^{(R)}$, and $Imprint^{(R)}$. 2. Impregum $F^{(R)}$ and $Zerosil^{(R)}$ showed the least number of voids on the surface of dental stone master cast. The number is inclosed in order of Provil $novo^{(R)}$ and Imprint 3. When abutment material is tooth, the number of voids on the surface of master cast was smallest compared with that of other abutment materials. The number of voids increased in order of casting metal, amalgam and composite resin 4. The number of voids on the surface of the dental stone master cast was smallest when Spannex $II^{(R)}$ was used, followed by $Cohere^{(R)}$ treated group and non-treated group. These results suggest that the difference in wettability caused by the types of rubber base impression materials as well as abutment materials can affect the number of voids. And the use of topical surfactant for rubber base impression materials can improve the wettability of the materials and enhance the accurate master cast which has fewer surface voids.